Child care practice as a risk factor of changes in nutritional status from normal to stunting in under five children - Leni Sri Rahayu; Debby Endayani Safitri; Indah Yuliana - (Alma Ata University Press, 2017)
ABSTRACTBackground: There was 9.5% of stunted infants aged 7-12 month changed to normal nutritional status at the age of 2 years. Integrated programs, health, hygiene, and stimulation have been successful to decrease the stuntingproportion by 17.2%. Objective: The aim of this study was to analyze the relationship between child care practice and changes in nutritional status from normal to stunting in under fivechildren.Methods: This study was a further analysis from the results of cohort data collection for 20 villages of the City and District of Tangerang in 2008-2011. The number of subject in this study were 571 n under five childre. Data were analyzed by chi-square test. Result: The results showed that the child care practice (OR=1.63, 95% CI ), hygiene and environmental sanitation (OR=1.63, 95% CI ) and health care aspects (OR=1.76, 95% CI ) were significantly associated with changes in nutritional status from normal to stunting.Conclusion: child care practice were associated with changes in nutritional status from normal to stunting in under five childrenKEYWORDS: stunting, child care practice, under-five children